Poor kids [videorecording (DVD)] - Neumann, Jezza, 1968-; Neumann, Jezza, 1968-; Lyman, Will, 1948- (PBS : PBS Distribution, 2013)
Profiles three young girls and their families living in poverty in the Quad Cities of Illinois and Iowa, a part of the U.S. hard hit by the economic downturn that began in the late '00s.